Phytochemical Screening and Antioxidant Activity of the Centella asiatica Leaf Extracts In a Variety of Solvents - Erlin Saalino; Halifah Pagarra (Jurusan Biologi Universitas Negeri Makassar, 2023)
Centella asiatica is a type of herbaceous plant that has many health benefits. This plant is a source of phenolic compounds, flavonoids, triterpenoids, alkaloids and tannins. This research aims to examine the phytochemical content and antioxidant potential of 70% ethanol extract of Centella asiatica leaf and the results of fractionation using 3 types of solvents with different polarities. Centella asiatica leaves were extracted by maceration method, then fractionation and phytochemical screening were carried out. The total phenolic content test was carried out using the Folin Ciocalteu method and the antioxidant activity test was carried out using the DPPH (2,2-diphenyl1-picrylhydrazyl) method. The yield of 70% ethanol solvent maceration, n-hexane fraction, ethyl acetate fraction and methanol fraction were 18.782%, 3.05%, 6.19%, and 92.46%, respectively. Phytochemical screening of 70% ethanol extract of Centella asiatica leaves contains flavonoids, tannins, phenolics, alkaloids and steroids. The nhexane fraction contains alkaloids, tannins, phenolics and triterpenoids. The ethyl acetate fraction contains flavonoids, saponins, tannins, phenolics, alkaloids and steroids. The methanol:water fraction contains alkaloids, flavonoids, saponins, tannins, phenolics and triterpenoids. The total phenolic content test of 70% ethanol extract, n-hexane fraction, ethyl acetate fraction and methanol:water fraction was 12.773 ± 0.479 mg GAE/g, 1.182 ± 0.124 mg GAE/g, 18.334 ± 0.305 mg GAE/g, and 10.211 ± 0.247 mgGAE/g, respectively. Antioxidant activity of 70% ethanol extract, n-hexane fraction, ethyl acetate fraction and methanol:water fraction with IC50 values of 7.4 ppm, 2122.5 ppm, 45.6 ppm and 126 ppm.